Humane and effective solutions to asylum asymmetries? "Vetting" and "monitoring" Syrians and Venezuelans in Argentina - Sybil Rhodes; Mäeliss Bodenan (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
In the context of restrictive immigration regimes and nationalist-populist politics, the international humanitarian obligation to consider migrants' claims for political asylum presents states with especially difficult challenges related to "vetting" and "monitoring" migrants. Given that these conditions are unlikely to end any time soon, some authors have suggested solutions to information asymmetries that might lead to effective and more humane outcomes to asylum and refugee crises. This paper evaluates one such proposal, the idea that migrants from "disfavored classes" be admitted in "circles of trust," groups of five or six people which could be held collectively responsible for the bad behavior of any individual member in the context of refugee and migrant policy in contemporary Argentina. Specifically, the paper compares a plan for Syrian refugees in place since 2015, and the reception of large numbers of Venezuelans since 2014. The paper concludes that "circles of trust" are fraught with perils, but that other non-traditional forms of vetting and monitoring might sometimes be humane and useful in particular situations.
Keywords: 330; Refugees; migrants; vetting; policy; monitoring; Argentina; circles of trust